Analysis Of Brand Image, Facilities And Promotions On Students Decisions In Choosing The Bachelor Of Management Study Program At Universitas Pembangunan Panca Budi - Rizco Rama Donni; Husni Muharram Ritonga (Utan Kayu Publishing, 2024)
This study was conducted on management students at Universitas Pembangunan Panca Budi Medan with the aim of analyzing brand image, facilities and promotions on students' decisions in choosing a bachelor's degree in management. The population of the study were 464 students of Universitas Pembangunan Panca Budi Medan, class of 2023, faculty of management, sampling was carried out by random sampling with the Slovin formula so that the number of samples were 82 respondents. The types of data used were primary and secondary data, data collection techniques using observation, questionnaires and documentation. Data analysis techniques were multiple linear regression, classical assumption tests and hypothesis tests. The results of the study showed that brand image, facilities and promotions partially and simultaneously had positive and significant effect on students' decisions in choosing a management study program. There was strong correlation between brand image, facilities and promotions on students' decisions to take management study program at Panca Budi Development University Medan. Students' decisions can be explained by brand image, facilities and promotions in taking management study programs by 39.1% and the remaining 60.9% can be explained by other variables not studied, such as tuition fees, motivation to study and so on.